Developing a measure of distress-promoting parent behaviors during infant vaccination: Assessing reliability and validity. Issue 1 (1st January 2018) - Pillai Riddell, Rebecca; Gennis, Hannah; Tablon, Paula; Greenberg, Saul; Garfield, Hartley
ABSTRACT: Background: Infants rely on their parents' sensitive and contingent soothing to support their regulation from pain-related distress. However, despite being of potentially equal or greater import, there has been little focus on how to measure distress-promoting parent behaviors. Aims: The goal of this article was to develop and validate a measure of distress-promoting parent behaviors for acute painful procedures (e.g., vaccinations) that could be used by researchers and clinicians. Methods: Following initial generation of measure items, focused group discussions were held with vaccinating clinicians to understand the measure's face, content, and ecological validity. Archival video footage ( n = 537 videos of infant-caregiver dyads during vaccination) was then coded using the measure of distress-promoting behaviors for 3 minutes post vaccine injection. Validity and reliability were examined using correlational analyses. Construct validity was assessed by convergent relationships with infant pain-related distress and divergent relationships were assessed with parent sensitivity and soothing-promoting behaviors. Results: The measure demonstrated both moderate to excellent interrater and test-retest reliability and convergent and divergent validity (absolute magnitude of r 's = 0.30 to 0.46). Conclusions: By demonstrating strong reliability and validity, this measure represents a promising new way to understand how caregivers interact with infants during painful procedures. Through focusing on distress promotion and using a format that may be coded both from video or in vivo, it is a feasible way to operationalize the impact of the caregiver on the infant's pain experience in both research and clinical settings.